2017
DOI: 10.1249/jsr.0000000000000346
|View full text |Cite
|
Sign up to set email alerts
|

Zany Over Zika Virus: An Overview of Diagnosis and Treatment Modalities

Abstract: Zika virus has been a recent international public health concern with outbreaks occurring in the Americas, Caribbean, and Pacific. The zoonotic infection is primarily spread to humans by the bite of an infected Aedes mosquito. The virus also can be transmitted via bodily fluids, sexual intercourse, and maternal-fetal vertical transmission. Asymptomatic presentation is common. If symptoms do occur, individuals display a low-grade fever, maculopapular rash, arthralgia, or conjunctivitis 2 to 7 d after infection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Before 2007, a few cases of infections were reported at different places in Asian and African countries. Changes in the last years, due to human activities and climate changes, likely induced adaptive evolution mutation in the RNA genome of ZIKV [6]. Furthermore, during 2014-2015, ZIKV infection spread in South and Central America, the Caribbean regions and northeastern parts of Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Before 2007, a few cases of infections were reported at different places in Asian and African countries. Changes in the last years, due to human activities and climate changes, likely induced adaptive evolution mutation in the RNA genome of ZIKV [6]. Furthermore, during 2014-2015, ZIKV infection spread in South and Central America, the Caribbean regions and northeastern parts of Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis of ZIKV infection can be made based on apparent pathology, presence of the vector in the area, ZIKV-associated neurological syndromes, epidemiological evidence, and results of serological and molecular tests (Singh et al, 2016 ). ZIKV has been shown to be transmitted through body fluids during sexual intercourse and vertically, from mother to fetus (Balm et al, 2012 ; Gourinat et al, 2015 ; Leung et al, 2015 ; Musso et al, 2015 ; Tognarelli et al, 2015 ; de M. Campos et al, 2016 ; Jacob, 2016 ; Moulin et al, 2016 ; Shinohara et al, 2016 ; Staples et al, 2016 ; Pyzocha et al, 2017 ). Clinical samples that can be used for diagnostic purposes comprises of serum, the umbilical cord of an infant, urine, nasopharyngeal swabs, saliva, brain tissue, amniotic fluid, CSF, and placenta.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies confirmed that, after 2015, approximately 1.5 million people in Brazil alone were infected with ZIKV, with almost 80% of cases asymptomatic but positive for viral RNA. Since 2007, more than 55 countries in the Americas, Asia, Africa, the Caribbean, and the Pacific region have reported cases with GBS syndrome, retinal/eye lesions, and/or increased incidence of microcephaly that were confirmed by RT-PCR, IgM ELISA, or neutralizing antibody-based serological tests (Carod-Artal, 2016 ; Pyzocha et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%